Anticancer Potential of Hesperidin against HEp-2 Laryngeal Carcinoma Cell Line in Comparison to Doxorubicin - El Wahed, Sara Abd; Hassabou, Nadia Fathy; Hamouda, Mai Abdelhalim (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Doxorubicin (DOX) is a drug that is frequently used to treat a variety of cancers. Unfortunately, in many situations, it is ineffective, and raising the dosage is restricted due to systemic toxicity. An important strategy to minimize the toxic effects of the above cited drug is to use co-adjuvant. A citrus flavonoid hesperidin (Hesp) has emerged as promising anticancer natural product and proved to be potent antioxidant agent. It suppresses cancer cell replicating by triggering apoptosis and cell cycle arrest. AIM: The study’s goal was to investigate anticarcinogenic effects of Hesp in comparison with DOX against HEp-2 laryngeal carcinoma cell line. MATERIALS AND METHODS: Five groups of HEp-2 cell line were included, two groups were subjected to Hesp and the other two groups were subjected to DOX, which was used as a reference drug, in addition to a control untreated group. Expression of Bcl-2 and p53 genes was evaluated. Furthermore, the cell cycle arrest and apoptotic induction were assessed. RESULTS: Hesp exerted anti-proliferative effects against HEp-2 cells which increase in time dependent manner. Gene profile analysis revealed highly statistically significant decrease of anti-apoptotic Bcl-2 expression and highly statistically significant increase of tumor suppressor gene p53 expression (p ˂ 0.01 and p ˂ 0.0001, respectively) for both tested drugs. CONCLUSIONS: Hesp proved potential anticancer effects with reducing cancer cell viability in HEp-2 cell line through cell cycle arrest and apoptotic mechanism. It could be used as a prodrug or coadjuvant in treatment of oral cancer.